The Value of Integrating South China Sea History and Culture into Higher Education (Journal of Global Arts Studies, 2024)
Background: The South China Sea culture is an important component of Chinese culture, containing rich folk resources and historical value, playing an important role in the inheritance and development of Chinese culture. Objective: By conducting in-depth research on the practical application of South China Sea history and culture in higher education, we aim to reveal its value in enhancing cultural confidence, promoting academic exchange, and promoting local development. Methods: This article adopts various research methods such as literature analysis, case study, and field investigation to deeply explore the value and significance of South China Sea history and culture in higher education. Results: Starting from the perspective of creating distinctive ideological and political courses through regional culture, combined with the rich educational functions of the South China Sea historical and cultural heritage, and integrating socialist core values. Explore the value of South China Sea history and culture in higher education, and analyze its positive impact on student growth, cultural inheritance, and regional development. Conclusion: The history and culture of the South China Sea can enrich students' knowledge system and improve their comprehensive quality in higher education. Incorporate the research and inheritance of the history and culture of the South China Sea into the curriculum system and teaching practice, providing students with a more comprehensive and in-depth learning experience.
Keywords: South China Sea；South China Sea history and culture；higher education；cultural heritage